Moderate Maternal Alcohol Exposure on Gestational Day 12 Impacts Anxiety-Like Behavior in Offspring - Rouzer, Siara K.; Cole, Jesse M.; Johnson, Julia M.; Varlinskaya, Elena I.; Diaz, Marvin R. (Frontiers in Behavioral Neuroscience, 2017)
Among the numerous consequences of prenatal alcohol exposure (PAE) is an increase in anxiety-like behavior that can prove debilitating to daily functioning. A significant body of literature has linked gestational day 12 (G12) heavy ethanol exposure with social anxiety, evident in adolescent males and females. However, the association between non-social anxiety-like behavior and moderate alcohol exposure, a more common pattern of drinking in pregnant women, is yet unidentified. To model moderate PAE (mPAE), we exposed pregnant Sprague-Dawley rats to either room air or vaporized ethanol for 6 h on G12. Adolescent offspring were then tested on postnatal days (P) 41-47 in one of the following four anxiety assays: novelty-induced hypophagia (NIH), elevated plus maze (EPM), light-dark box (LDB), and open-field (OF). Our findings revealed significant increases in measures of anxiety-like behavior in male PAE offspring in the NIH, LDB and OF, with no differences observed in females on any test. Additionally, male offspring who demonstrated heightened anxiety-like behavior as adolescents demonstrated decreased anxiety-like behavior in adulthood, as measured by a marble-burying test (MBT), while females continued to be unaffected in adulthood. These results suggest that mPAE leads to dynamic changes in anxiety-like behavior exclusively in male offspring.